The relationship between orthodontic tooth movement and common periodontal disorders - Witjaksono, Widowati; Tin, Myo Han (Malaysian Journal of Medical Science, 2015)
Background: Orthodontic treatment requires remodeling of the periodontal tissues, including the periodontal ligament fibers and alveolar bone in order to straighten the misaligned teeth. The effect of orthodontic treatment is apparent esthetically but the effect to the periodontal condition is still questionable. Aim: To investigate the effects of orthodontic treatment on periodontal condition among the orthodontic patients attending KOD, IIUM. Materials and Methods: Patients who were undergone orthodontic treatment at the Orthodontic Specialist Clinic KOD, were selected based on the inclusion and exclusion criteria. The periodontal health of each patient was examined clinically using the Basic Periodontal Examination (BPE) method using the WHO probe (621 probe) around the index teeth. The BPE scores were taken again 6 months, a year and 2 years after the beginning of orthodontic treatment. Risk estimation (Risk Ratio) and chi square test will be used for data analysis. Results: This clinical experimental study showed that a thorough therapy of the patients with orthodontic case can be treated successfully with simultaneously control of periodontal condition Conclusion:After undergoing orthodontic treatment, only 1 sextant has a significant difference in the effect of orthodontic treatment on periodontal condition. Therefore, orthodontic treatment may not be a primary causal factor for a decline in the periodontal condition.